2005
DOI: 10.1007/s11307-005-0025-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined I-124 Positron Emission Tomography/Computed Tomography Imaging of NIS Gene Expression in Animal Models of Stably Transfected and Intravenously Transfected Tumor

Abstract: I-124 PET/CT in combination with NIS allows the tracking of stably transfected tumors or intravenously transfected tumors. Combined modality imaging using PET/CT allows accurate and non-invasive imaging of the distribution and gene expression of a replicating viral vector in living systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 28 publications
(20 reference statements)
0
38
0
2
Order By: Relevance
“…Potassium perchlorate (KClO 4 ) has been used in rats 6-18 hours following injection of 125 I and shown to reduce the 125 I thyroid/blood ratio when thyroid peroxidase is inhibited (51,52). 124 I positron emission tomography/computerized tomography (PET/CT) has been used rarely to evaluate uptake and discharge of iodide in rodent thyroids in vivo (53).…”
Section: And Recommendation 3amentioning
confidence: 99%
See 1 more Smart Citation
“…Potassium perchlorate (KClO 4 ) has been used in rats 6-18 hours following injection of 125 I and shown to reduce the 125 I thyroid/blood ratio when thyroid peroxidase is inhibited (51,52). 124 I positron emission tomography/computerized tomography (PET/CT) has been used rarely to evaluate uptake and discharge of iodide in rodent thyroids in vivo (53).…”
Section: And Recommendation 3amentioning
confidence: 99%
“…The sensitivity of PET is higher than that of a scintillation camera, as well as the contrast and spatial resolution (53). For accurate thyroid imaging in rats, the combination of microPET and micro computed axial tomography with 124 I is necessary (Fig.…”
Section: Commentarymentioning
confidence: 99%
“…PET combined with computerized tomography has a ten times higher resolution than conventional imaging and permits precise anatomical localization. In an attempt to develop this promising approach, two studies have demonstrated that hNIS expression in tumor xenograft models can be monitored by PET after intravenous injection of 124 I, demonstrating the potential of this approach for noninvasive imaging (128,129).…”
Section: Nis Gene Transfermentioning
confidence: 99%
“…Dieses Isotop wird ebenfalls in Radiopharmaka inkorporiert verwendet. [182] Der wesentliche Vorteil ist hierbei seine län-gere Halbwertszeit gegenüber der von 18 F. 135 I ist ein in Kernreaktoren häufig gebildetes Isotop.…”
Section: Angewandte Chemieunclassified